The identities of Cancer arenarius Toreen, in Osbeck, 1765, Cancer arenarius Zimmermann, in Cavolini, 1792, Cancer (Mantis) arenarius Herbst, 1793, and Cancer (Gammarellus) arenarius Herbst, 1793, and other names associated with the genus Ocypode Weber, 1795 (Crustacea: Amphipoda, Decapoda, Stomatopoda) - Low, M.E.Y. (2014)
Zootaxa